THU0516 Longer term outcomes of crmo in a tertiary adolescent and young adult rheumatology centre in the uk. (15th June 2017) - Clark, KEN; Josephs, F; Daly, N; Ioannou, Y; Murphy, CL; Sen, D
Abstract : Background: Chronic relapsing multifocal osteomyelitis (CRMO) is a rare autoinflammatory bone condition presenting primarily in children and adolescents. It characteristically affects the epiphysis and metaphysis of long bones, and presents with bony pain, local swelling and warmth. Objectives: The aim of this study was to collate our tertiary adolescent rheumatology centre's experience of managing patients with CRMO, and establish their longer term outcomes, possible by the fact we have a cohort of patients with CRMO under long-term follow-up. Methods: We carried out a retrospective case note review of all patients who are known to our service with a diagnosis of CRMO, presenting between age 13–20. Results: In total 17 patients were identified as having CRMO, presenting between 1999 and 2015. 10 patients were female, and 7 patients male. The median age of initial symptoms, and age of presentation was 12 years (range1–16 years). Median duration of follow up is 4.75 years (range 1–16.5 years). Since initial diagnosis, 3 patients evolved into a SAPHO (synovitis, acne, pustolosis, hyperostosis, osteitis) phenotype, 3 an ERA (enthesitis related arthritis) phenotype and 2 patients developed oligoarticular juvenile idiopathic arthritis (JIA). 35% of patients have a purely unifocal disease, and 65% have multifocal disease as confirmed by whole body MRI. 70.5% patients had recurrent episodes of inflammation, while 29.5% of patients had only one flare and then reached remission (either clinical or confirmed with MRI). 15 patients had their diagnosis confirmed with biopsy, while 2 did not due to site of disease. Their diagnosis is assumed based on clinic impression, and typical radiographic findings. Sites of disease confirmed in our patients include lower limbs (70% patients), upper limbs (35% patients), clavicle (29.4%), mandible (17.6%) and spine/pelvis (23.5%). All patients were treated with NSAIDs. In terms of treatments used since diagnosis, 76% patients have been on methotrexate (MTX), 47% had one infusion of pamidronate, and 23% required more than one infusion of pamidronate. Other medications include sulfasalazine (SSZ), azathioprine, risedronate and anti-TNFs (adalimumab, etanercept and infliximab). On last clinic review, with or without imaging, 35% of patients continue to have active disease. Currently 29% patients are on MTX alone, 23% patients are on adalimumab and MTX, and 35% are only maintained on NSAIDS. Of those without active disease 5 patients (45%) are not on any DMARD or biologic therapy. Conclusions: We present here our experience of managing adolescent patients with CRMO. The perceived wisdom is that CRMO is a self-limiting disease which eventually goes into remission. However our centre's experience is that nearly 50% of our patients have a disease which evolves into another systemic autoimmune disease, mainly SAPHO, polyarticlar or enthesitis related JIA. Previous case series have suggested only 0–30% of patients' disease evolves. This may be a reflection of our older cohort of patients, who are only referred to our service with ongoing disease. The majority of patients have a recurrent and multifocal course of disease. The most common site of disease was in the lower limbs. All patients were treated with NSAIDS, and a combination of DMARDS, bisphosphonates and biologic agents have been used, which has resulted in remission of disease in the majority of patients. Disclosure of Interest: None declared